Catalytic supercritical water gasification of oil palm frond biomass using nanosized MgO doped Zn catalysts - Mohd Sufri Mastuli; Norlida Kamarulzaman; Muhd Firdaus Kasim; Annie Maria Mahat; Yukihiko Matsumura; Yap, Taufiq Yun Hin (Elsevier B.V., 2019)
In this work, nanosized MgO doped Zn catalysts (Mg1-x Znx O; x = 0.05, 0.10, 0.15, 0.20) were catalyzed the supercritical water gasification (SCWG) of oil palm frond (OPF) biomass for hydrogen production. Increased the amount of Zn in the catalyst enlarged the crystallite size, thus, reduced the surface area. Interestingly, all the synthesized catalysts have crystallite sizes of less than 50 nm. In-depth Rietveld refinement analysis revealed that the enlargement of the crystallite size is due to the phenomenon of cell expansion when the smaller Mg2+ ions being replaced by the larger Zn2+ ions during the doping process. Increased the Zn content also improved the basicity properties. Among the synthesized catalysts, the Mg0.80 Zn0.20 O exhibited the highest total gas volume of 213.5 ml g-1 of the biomass with 438.1% of increment in terms of H2 yield. The metal oxide doped materials serve as a new catalyst structure system for the SCWG technology.